Miliusa refracta (Annonaceae): a new species from Vietnam - Shi, Zhiyuan; Vu, Quang Nam; Hou, Xueliang (Phytotaxa, 2026)
We describe a new species of Miliusa from Vietnam that is like M. balansae and M. sinensis but differs in several characters. Molecular phylogenetic analyses show that it is distinct from the other Miliusa species, corroborating its recognition as a distinct species. Additionally, ten species of Miliusa from Vietnam have been confirmed, and a dichotomous key for these is provided.